Possible biological mechanisms of sudden sniffing death syndrome due to toluene exposure - Vural, Mutlu; Ögel, Kültegin (Journal of Dependence, 2008)
Sudden sniffing death syndrome due to toluene exposure is an outcome of the progressive social problem of intentional substance inhalation abuse. There is limited evidence about the biological mechanisms of toluene-induced sudden death, although toluene exposure is prevalent as a volatile solvent used in industrial settings. Toluene is known to possess toxic effects on many organs, most dramatically on the heart. Sudden death may result directly from ventricular tachyarrhythmias and severe bradycardia due to the cardiac toxicities of toluene. Toluene may also result in cardiomyopathy, myocarditis, and myocardial infarction, all of which are known to be associated with sudden death. In addition to its toxicity on the heart, this solvent is also toxic to the lungs, kidneys, nervous system, and bone marrow, which may contribute to the mechanism of sudden sniffing death due to toluene exposure. For these reasons, toluene-induced sudden death is discussed in this paper as a complex combination of the toxicities of toluene to the heart and other organs.